2019
DOI: 10.21608/ejh.2019.19045.1195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of platelet rich plasma and hyaluronic acid on ketamine-induced cystitis in albino rats : A histological and immunohistochemical study.

Abstract: Background: ketamine induced cystitis (KIC) is commonly occurred in ketamine abusing individuals. It is associated with damage in the lining of the bladder and lower urinary tract symptoms. Platelets rich plasma (PRP) is attractive therapeutic line in regenerative medicine. Hyaluronic acid (HA) has many beneficial therapeutic effects in treatment of different types of cystitis. Objective: to evaluate the effect of PRP and HA on ketamine induced cystitis in adult male rats. Materials and Methods: Forty-four adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The active form of NF-κB is a crucial player in the process of inflammation 20 . Its expression was mainly observed in the urothelium and the lamina propria of PRP-treated cystitis 151 ; likewise to our study which showed expression of NF-KB in the urothelium and inflammatory cells of the PRP-treated groups. However, the decreased expression of NF-κB in the group treated with PRP and antibiotics was not reflected in the histopathology of the bladder mucosa as there were still erosions in the urothelium.…”
Section: Immunohistochemical Evaluationsupporting
confidence: 89%
See 1 more Smart Citation
“…The active form of NF-κB is a crucial player in the process of inflammation 20 . Its expression was mainly observed in the urothelium and the lamina propria of PRP-treated cystitis 151 ; likewise to our study which showed expression of NF-KB in the urothelium and inflammatory cells of the PRP-treated groups. However, the decreased expression of NF-κB in the group treated with PRP and antibiotics was not reflected in the histopathology of the bladder mucosa as there were still erosions in the urothelium.…”
Section: Immunohistochemical Evaluationsupporting
confidence: 89%
“…However, PRP treated group was remarkably improved in which the normal thickness of urothelium was maintained and edema was regressed. Similarly, An earlier investigation revealed that PRP had a positive effect on ketamine-induced cystitis in rats in which the urothelium thickness was increased but congestion and inflammatory cell infiltration were still observed in the urinary bladder 151 . In the present study, all groups treated with PRP showed urothelium proliferation which is critical in maintaining a functional barrier against urinary toxic substances and bacteria 60 .…”
Section: Histopathological Evaluationmentioning
confidence: 66%